Community engagement in global health research that advances health equity. (23rd July 2018) - Pratt, Bridget; de Vries, Jantina
Abstract: Community engagement is gaining prominence in global health research. So far, a philosophical rationale for why researchers should perform community engagement during such research has not been provided by ethics scholars. Its absence means that conducting community engagement is still often viewed as no more than a 'good idea' or 'good practice' rather than ethically required. In this article, we argue that shared health governance can establish grounds for requiring the engagement of low‐ and middle‐income country (LMIC) community members in global health research, where such research aims to help reduce health disparities. This philosophical basis has important implications for the ethical goals ascribed to engagement and the approach adopted to undertake it. We suggest the ethical goals of engagement in equity‐oriented global health research should include: (a) generating research topics and questions that reflect the key problems disadvantaged groups face in accessing healthcare, services and broader social determinants of health and (b) promoting the translation of research findings into policy and practice in ways that benefit the health of disadvantaged groups. We propose engagement practice should have the following features: deliberation with LMIC community members to make a range of project decisions, beginning with setting research topics and questions; inclusion of members of disadvantaged groups and those with the power to change policy and practice to benefit them; and purposeful structuring of deliberations to minimize the impact of power disparities between LMIC community members. Finally, we reflect on how these features differ from those typical of much current community engagement practice in LMICs.